Global research landscape and science mapping of age-friendly communities: A bibliometric analysis on healthy aging and community resilience (2015–2025) - Sukardin Sukardin; Milya Novera; Sumana Lama; Omawale Odoyemi; Altaf Hussain (Yayasan Pendidikan Kardin Assidiq, 2026)
Background: The global demographic transition underscores the necessity for the development of Age-Friendly Communities (AFCs) aimed at promoting healthy ageing and enhancing community resilience. This study examines the intellectual framework surrounding AFC research from 2015 to 2025, to inform nursing scholarship and public health initiatives. Methods: A comprehensive bibliometric analysis was performed on 245 peer-reviewed articles obtained from the Scopus database, covering the timeframe from 2015 to 2025. This targeted selection adhered to stringent inclusion criteria that emphasize the direct intersection of four key domains: